Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Pada Perusahaan Manufaktur Sub Sektor Food And Beverage Yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Extevanus, Leonaldo; Habiburahman, Habiburahman (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research aims to determine the influence of Value added Capital employed (VACA), Value added Human capital (VAHU) and Structural capital Value added (STVA) together on the Financial Performance of Manufacturing Companies in the Food and Beverage Sub Sector listed on the Indonesia Stock Exchange for the period 2019-2022. The data source in this research is secondary data, namely the annual financial reports (Annual Report) of food and beverage companies listed on the Indonesia Stock Exchange which report their finances for 2019-2022. This analysis uses calculations through statistical methods. Based on its type, this research uses a quantitative method approach with panel data analysis tools. Based on the population and sample, this research focuses on manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period 2017 to 2020, namely 12 companies. Value added capital employed (VACA), value added human capital (VAHU) and structural capital value added (STVA) together influence the return on assets of manufacturing companies in the food and beverage sub-sector listed on the IDX for the 2019-2022 period.